Optimalisasi Kecerdasan Bahasa Anak Usia Dini melalui Metode Bermain Peran - Indah Fajrotuz Zahro; Nurul Azizah Ria Kusrini (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2018)
Language is one of the important aspects for early childhood development. Language functions as a means of communication as well as being an important means for the lives of children. It is dangerous to be a means for children to be able to interact with each other, share their experiences, and be able to improve intellectually, namely in order to develop their language knowledge and skills. For early childhood it is a period of development that must be fostered and developed so that they can make full use of their language skills. If the guidance, direction, and handling are not appropriate or even not obtained by the child causes language development that is not in accordance with what is expected by parents at home or by educators at school. The methods that can be done to stimulate and optimize children's language intelligence, including the method of question and answer, storytelling, tourist visits and play play (dramatic play). The role playing method consists of playing the role of macro and micro by going through the stages of playing an artificial role, playing with the object, pretending to be related to actions and circumstances, perseverance and oral communication. Based on data analysis and discussion, information can be obtained that the method of playing drama (play dramatically) / role playing is carried out in several stages, namely identifying figures, determining story settings, interpreting stories and values ​​contained, reflection and observation. The application of this technique is expected to provide optimization of early childhood language intelligence.